2009
DOI: 10.1002/ange.200805014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling, Synthesis, and Biological Evaluation of Macrocyclic Calpain Inhibitors

Abstract: The introduction of a macrocycle into a biologically active peptide can increase potency [1,2] and selectivity [3] by reducing the entropic penalty of inhibitor-enzyme binding. The incorporation of macrocycles in peptides has been used to mimic secondary structure, such as extended b-strand-like and bent b-turn-like conformations. [3,4] The challenge is to devise protocols for the design, evaluation, and synthesis of macrocyclic templates that provide access to families of inhibitors. [5] Such templates should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…In their search for compounds to inhibit the cysteine protease calpain, toward the prevention of cataractogenesis, Stuart et al designed constrained bridged peptides with the goal of holding the ligand in a β-strand-like conformation. 58,59 The designed compounds were then subjected to an MCMM conformational search in order to determine the likelihood that the ligands would maintain the desired conformation, indicated by the percentage of conformers with a characteristic β-strand shape. Interestingly, though macrocyclic ligands with a 16member macrocycle possessed nearly 100% β-strand character, the most potent compound in the series, CAT811, displayed only 8% β-strand character.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…In their search for compounds to inhibit the cysteine protease calpain, toward the prevention of cataractogenesis, Stuart et al designed constrained bridged peptides with the goal of holding the ligand in a β-strand-like conformation. 58,59 The designed compounds were then subjected to an MCMM conformational search in order to determine the likelihood that the ligands would maintain the desired conformation, indicated by the percentage of conformers with a characteristic β-strand shape. Interestingly, though macrocyclic ligands with a 16member macrocycle possessed nearly 100% β-strand character, the most potent compound in the series, CAT811, displayed only 8% β-strand character.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…B. Angiotensin-umwandelndes Enzym (ACE), neutrale Endopeptidase NAP (wie 25), Thermolysin, Aminopeptidase, MMP1, -3, -8, -9 (wie 26), TNFa-umwandelndes Enzym (TACE)), und Cystein-Proteasen wie Calpaine (wie 27). [31] [32] Es gibt eines großes, noch unerschlossenes Potenzial für den Entwurf von b-Strang-und b-Faltblatt-Mimetika, mit denen die Protein-Protein-Wechselwirkungen gestçrt oder die Bindung eines der Partner nachgeahmt werden soll. [6,7] PPI spielen sich oft an großen polaren Regionen der Oberfläche mit nur flachen Einbuchtungen ab, die oft nicht effektiv von kleinen hydrophoben Molekülen besetzt werden…”
Section: Einführungunclassified
“…Mit 84 wurde ein Antagonist des onkogenen ternären NOTCH-1-Transkriptionsfaktor-Komplexes entwickelt. Das 15 Aminosäuren lange Peptid von MAML1 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Abbildung 15. Verschieden lange Alkyllinker zwischen den Positionen i!i + 3, i!i + 4 und i!i + 7.…”
Section: Cyclische Peptidhelicesunclassified
“…18 A SAR by Abell et al on macrocyclic peptide aldehyde inhibitors of ovine calpain found that the addition of an aldehyde to a peptide macrocycle can increase potency as much as ∼1000-fold. 19 The results of Abell et al combined with the proteasome's flexible S 2 and S 4 pockets suggest that a macrocyclic peptide aldehyde with a suitable peptide sequence will yield a potent and selective inhibitor of the 20S proteasome. Other desirable pharmacological properties introduced by the macrocycle include increased metabolic stability, cellular uptake, and tissue distribution.…”
mentioning
confidence: 99%